Diversity of aquatic plants and macroinvertebrates and their spatial patterns in a Himalayan Watershed, Central Nepal - Upadhyay, Kanchan Devi; Mainali, Janardan; Ghimire, Narayan Prasad (Aquatic botany, 2022)
Spatial patterns of aquatic species are indicative of the quality of the in-stream water quality as well as that of the surrounding watershed. The relationships among aquatic species diversity, water quality, and watershed characteristics are not well explored in the Himalayan watershed. In this work, we analyzed the impacts of in-stream water quality, watershed socio-environmental conditions, and spatial predictors on the species composition of aquatic plants and macroinvertebrates. We collected macrophytes, phytoplankton, and macro-invertebrate samples and measured with dissolved oxygen and electrical conductivity of the lakes and rivers of the Setikhola watershed, Central Nepal. The watershed landscape variables such as landcover types, population density, and topography along with spatial factors derived from the spatial connectivity matrices were used as explanatory variables to explore species composition using redundancy analysis. We reported 39 macrophyte species, 105 phytoplankton species, and 35 families of macroinvertebrates. The macrophyte species belonging to the family Potamogetonaceae were dominant, as were the phytoplankton species belonging to Bacillariophyceae; most macro-invertebrates belonged to families in the order Diptera. We report a significant impact on watershed human population density as well as the electrical conductivity of the water on aquatic species composition. Inclusion of spatial factors increased model predictive performance of macrophyte and phytoplankton species composition. This study can help in a robust understanding of aquatic systems in relation to corresponding socio-environmental settings to manage them with optimal benefits for the ecosystems and people. •Setikhola watershed holds 39 macrophyte, 105 phytoplankton species, and 35 families of macro-invertebrates.•Eutrophication indicative taxa were associated with human impacts.•Rivers in the watershed have higher biodiversity than the lakes.•Spatial predictors increased model performance of macrophytes and phytoplankton.